Visceral (hepatosplenic) form of bartonellosis - A. L. Rossina; S. B. Chuelov; N. V. Kondratenko; A. V. Tebenkov; E. V. Grushitskaya; N. V. Zinovieva; E. V. Sudarikova; Yu. V. Petrova; O. V. Shamsheva (Детские инфекции (Москва))
The relevance of the problem of the visceral (hepatosplenic) form of bartonellosis in children is due to the fact that the disease is one of the causes of the development of the so-called «fever of unknown origin», manifested by the formation of focal lesions in the internal organs and requires antibacterial therapy. The purpose of the work is to study the data available in the literature regarding the visceral (hepatosplenic) form of bartonellosis, and to demonstrate our own clinical cases. Materials and methods: a review of domestic and foreign literature over the past 10 years was carried out, including Internet resources, and our own clinical observations of children with the visceral (hepatosplenic) form of bartonellosis were presented. Conclusion. The visceral (hepatosplenic) form of bartonellosis in children occurs with febrile fever, accelerated ESR, increased levels of C-reactive protein, visualization of multiple foci in the liver and spleen, and possible damage to the lungs and kidneys. Treatment is with antibiotics; usually a combination of different drugs.